Revealing electrical and mechanical performances of highly oriented electrospun conductive nanofibers of biopolymers with tunable diameter - Munawar, Muhammad; Schubert, Dirk W. (International Journal of Molecular Sciences, 2021)
The present study outlines a reliable approach to determining the electrical conductivity and elasticity of highly oriented electrospun conductive nanofibers of biopolymers. The highly oriented conductive fibers are fabricated by blending a high molar mass polyethylene oxide (PEO), polycaprolactone (PCL), and polylactic acid (PLA) with polyaniline (PANi) filler. The filler‐matrix interaction and molar mass (M) of host polymer are among governing factors for variable fiber di-ameter. The conductivity as a function of filler fraction (φ) is shown and described using a McLach-lan equation to reveal the electrical percolation thresholds (φc) of the nanofibers. The molar mass of biopolymer, storage time, and annealing temperature are significant factors for φc. The Young’s modulus (E) of conductive fibers is dependent on filler fraction, molar mass, and post‐annealing process. The combination of high orientation, tunable diameter, tunable conductivity, tunable elas-ticity, and biodegradability makes the presented nanofibers superior to the fibers described in pre-vious literature and highly desirable for various biomedical and technical applications.
Created from Fastlane, Scopus look-up
Keywords: Biomed-ical; Electrical percolation threshold; Fiber diameter; Orientation; Young’s modulus